Dinamika Indeks Pembangunan Manusia di Provinsi Jawa Barat Tahun 2018-2022 - Sheety, Vera Vernanda; Sitti Retno Faridatussalam (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to find out the influence of the Poverty Severity Index, Number of Poor Population, PDRB per Capita, and Number of Aid Recipients on the Human Development Index in West Java in 2018-2022. The research carried out is a type of quantitative descriptive research. The research tool used is panel data regression analysis with the selected Fixed Effect Model (FEM). Based on the panel data regression, it is explained that the Poverty Severity Index and the Number of Poor People have a negative effect on the Human Development Index, while PDRB per Capita and the Number of Aid Recipients have a positive effect on the Human Development Index in West Java Province in 2018-2022.